2020
DOI: 10.1016/j.molcel.2020.06.033
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Whole-Genome Analysis of Sister-Chromatid Contacts

Abstract: Sister-chromatid cohesion describes the orderly association of newly replicated DNA molecules behind replication forks. It plays an essential role in the maintenance and faithful transmission of genetic information. Cohesion is created by DNA topological links and proteinaceous bridges, whose formation and deposition could be potentially affected by many processes. Current knowledge on cohesion has been mainly gained by fluorescence microscopy observation. However, the resolution limit of microscopy and the re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 73 publications
0
26
0
Order By: Relevance
“…After 12 h (~25 generations) of incubation, cells were plated on LB agar containing Sm, Km and Amp and ~890,000 colonies were scraped to collect as the ‘output’ library. NGS library preparation, including gDNA preparation, MmeI digestion, adapter ligation and PCR amplification, was carried out as described in [ 22 ]. Three independent libraries were prepared with distinct ‘barcodes’ and subjected to independent Illumina sequencing twice, which was carried out at the I2BC NGS facility (Gif-sur-Yvette, France).…”
Section: Methodsmentioning
confidence: 99%
“…After 12 h (~25 generations) of incubation, cells were plated on LB agar containing Sm, Km and Amp and ~890,000 colonies were scraped to collect as the ‘output’ library. NGS library preparation, including gDNA preparation, MmeI digestion, adapter ligation and PCR amplification, was carried out as described in [ 22 ]. Three independent libraries were prepared with distinct ‘barcodes’ and subjected to independent Illumina sequencing twice, which was carried out at the I2BC NGS facility (Gif-sur-Yvette, France).…”
Section: Methodsmentioning
confidence: 99%
“…Samples for Tn-seq analysis were prepared as described ( Espinosa et al 2020 ). Libraries were paired-end sequenced in a Next-Seq (Illumina).…”
Section: Methodsmentioning
confidence: 99%
“…Previous works showed that the choreography of chromosome segregation restricts the activity of FtsK to the terminus region of the two V. cholerae chromosomes, suggesting that FtsK could not drive integration at the lacZ locus (Figure S2, (25)(26)(27)(28)). Correspondingly, no dif1specific integration events were observed at the lacZ locus with XafTmini-TLCΦ libraries.…”
Section: Xaft Drives the Integration Of Any Attp Site Harbouring The Same 5 Th Xerd-arm Bp Than Dif1mentioning
confidence: 95%